Revised Code of Ordinances of the City of McKinney, Texas, Primary Sources Page 5, Image 6 (1899) Ordinances of the City of McKinney, Disturbance of the Peace, § 1. - (:unkn) unknown (My University, 1899)
That if any person shall go into or near any public place, or into or near any private house and shall use loud and vociferous or obscene, vulgar or indecent language or swear or curse, or yell or shriek or expose his person or rudely display any pistol or other deadly weapon in a manner calculated to disturb the inhabitants of such public place or private house, he shall be fined in any sum not exceeding one hundred dollars.
Keywords: BRANDISHING